Erratum to: Search for squarks and gluinos in final states with one isolated lepton, jets, and missing transverse momentum at √s=13 TeV with the ATLAS detector - Aad, Georges; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Schöning, André; et al. (The European physical journal. C, Particles and fields, 2021)
A correction to this paper has been published: 10.1140/epjc/s10052-021-09344-w